Tahfiẓ Al-Qur'an as Brand Image of Modern Islamic Education in Lombok - Hilmi, Muhamad; Nasir, Mohamad Abdun; Saparudin, Saparudin; Dahlan, Fathurrozi; Saharudin, Saharudin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research explores the widespread and trending phenomenon of al-Qur'an memorization (tahfiẓ) programs in Islamic education, encompassing traditional and modern settings such as Islamic boarding schools and public schools. Using a qualitative approach and drawing on Kotler's (2002) and Keller's (2001) brand image theory, data is collected through observation, interviews (with key figures in educational institutions, including leaders, teachers, parents, students, alumni, and government agencies in West Nusa Tenggara), and documentation. The findings highlight distinct types of tahfiẓ programs in the three selected educational institutions: Al-Aziziyah Islamic Boarding School requires the precise memorization of the entire Qur'an (30 chapters), Abu Hurairah Islamic Boarding School integrates the program within the formal curriculum, covering 13 chapters, and SDIT Anak Sholeh Mataram includes the program in the formal curriculum, completing two chapters (30 and 29). Theological, pragmatic, and sociological factors influence public responses to these institutions. The study suggests that the theological aspects play a significant role in shaping the perception of the Qur'an tahfiẓ program as an Islamic educational brand, which extends beyond the attributes, benefits, values, culture, personality, and users emphasized in existing brand image theories.